Edukacja tubylcza a szkolnictwo głównego nurtu – konteksty teoretyczne - Gmerek , Tomasz (Studia Edukacyjne, 2020)
The article deals with the issue of the relation between indigenous education and mainstream schooling in contemporary multicultural societies. Particular emphasis was placed on reconstructing educational practices that is implemented toward indigenous minorities. An attempt was made at examining the relationship between schooling, language policy, teachers education and revitalization and development of languages, cultures, traditions and ethnic identity of indigenous minorities.